Magnetic resonance imaging of Baló's concentric sclerosis: Literature review and presentation of two focused cases. Issue 1 (30th September 2020) - Ballini, Chiara; Destro, Francesco; Garofalo, Paolo; Suri, Jasjit S.; Ercoli, Tommaso; Muroni, Antonella; Caddeo, Giancarlo; Qi, Yang; Defazio, Giovanni; Saba, Luca
Abstract: The aim of this study was to describe two cases of Baló's concentric sclerosis, and to review the state‐of‐the‐art literature. This dissertation is the result of a critical analysis matching the literature and our professional experience. Data were synthesized into a narrative review. BCS is often referred to as a variant of multiple sclerosis (MS). It is still unclear whether BCS is an acute variant of MS or a distinct entity that happens to coexist with MS. BCS and MS‐like lesions might be present at the same time. BCS lesions are characterized by a large concentric "onion‐like" shape on MRI T2‐weighted images composed of alternating hypointense and hyperintense layers. On contrast‐enhanced T1‐weighted images, BCS active lesions usually show an enhancing and non‐enhancing pattern. The advancing edge of demyelination could be represented by peripheral restricted diffusion and contrast enhancement. Baló's lesions is mainly found in the supratentorial white matter; however; the cerebellum, the brainstem and the spinal cord might be affected as well. The present two cases both showed onion‐like lesions; case 1 showed typical BCS features, whereas case 2 was atypical and could be classified as probably BCS or as a BCS‐like lesion in the course of MS. It is important for radiologists to be able to recognize this type of lesion and to cooperate with clinicians to help them carry out earlier diagnosis and treatment, determining a better clinical outcome for patients affected by BCS, even without histological confirmation, which is still considered the gold standard. Abstract : This review aims to describe two cases of Balò's Concentric Sclerosis (BCS) and to review the state‐of‐the‐art literature. Through the analysis of current imaging practice, our purpose is to help clinicians reach early diagnosis, thus enhancing the chances of a more successful outcome for the patients.